MOVING ARCHITECTURE: AESTHETICS AROUND THE CHANGING CONTEXT AND STATUS OF CONSTRUCTIONS - Somhegyi, Zoltán (The Nordic Journal of Aesthetics, 2022)
One of the primary and most typical features of a piece of architecture is its stability, its fixed and anchored state. It is therefore surprising and, at the same time, aesthetically inspiring and intellectually exciting when buildings are moved. In the present study I examine the agency of transportation and the aesthetic consequences of such translocations in three art projects. First, I analyse the work of the Norwegian Marianne Heske, the Georgian Vajiko Chachkhiani, and the Finn Anssi Pulkkinen. I lay out the aesthetic implications of the transformative decontextualization caused by the relocation of the original structure. In the second part of the paper, I present the main aspects that connect these otherwise different projects and explain why the complex and costly transportation of these pieces of architecture is relevant and justified.